Factors influencing range contraction of a rodent herbivore in a steppe grassland over the past decades. Issue 2 (14th February 2022) - Bai, Defeng; Wan, Xinru; Li, Guoliang; Wan, Xinrong; Guo, Yongwang; Shi, Dazhao; Zhang, Zhibin
Abstract: Climate warming and human disturbance are known to be key drivers in causing range contraction of many species, but quantitative assessment on their distinctive and interactive effects on local disappearance is still rare. In this study, we examined the association of climate warming and human disturbance stressors with local disappearance probability of Brandt's voles ( Lasiopodomys brandtii ) in a steppe grassland in northern China. We used logistic generalized additive models to quantify the relationship between local disappearance probability of Brandt's voles and environmental variables. The year following the last observation year was used to estimate the disappearance threshold of Brandt's voles. We projected the distribution change of Brandt's voles under future climate warming scenarios. We found climate warming attributed to local disappearance and range contraction for southern populations of Brandt's voles from 1971 to 2020. Human stressors and high vegetation coverage increased the probability of local disappearance of voles in years of abundant precipitation. The southern boundary retreated northward at a speed of 99.0 km per decade with the temperature rise of 0.36°C. The disappearance threshold of maximum air temperature of Brandt's voles in the warmest month (27.50 ± 1.61°C) was similar to the lower critical temperature of its thermal neutral zone. Our study suggests that the rapid climate change over the past decades contributed to the range contraction of its southern boundary of this keystone species in the steppe grassland of China. It is necessary to take actions to preserve the isolated populations of Brandt's voles from the effects of accelerated climate change and human disturbance. Abstract : We found climate warming attributed to local disappearance and range contraction for southern populations of Brandt's voles from 1971 to 2020. The southern boundary of Brandt's voles retreated toward the north pole at a speed of 99.0 km per decade with the temperature rise of 0.36°C.